Separated Subject Curriculum (Curriculum in Learning Islamic Religious Education at Darussalam Boarding School Purwokerto) - Muzajjad Faqihudin, Ahmad (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The curriculum is an important element that acts as a guide to achieve maximum and quality educational results. One of the implementations of the curriculum in learning Islamic agam education is the Separated Subject Curriculum. Darussalam Islamic boarding school applies Separated Subject Curriculum in learning Islamic religious education materials such as nahwu, shorof, Arabic, fiqh, aqidah akhlah, etc. The advantages of using the Separated Subject Curriculum, the students focus on by one Islamic religious education materials, a more detailed understanding, more broadly scientifically. As for the aspects of the shortcomings of applying the Separated Subject Curriculum, it takes a longer time. The purpose of this study is to find out and get to know Islamic education at the Darussalam Islamic boarding school. The research method used is qualitative, using a descriptive methodology. The presentation of data is carried out by qualitative analysis. The results showed that the implementation stage of separated subject curriculum in learning Islamic religious education has advantages and disadvantages. So that in facing obstacles, pesantren are able to maintain the quality of education to the students of Darussalam Islamic boarding school.